1991
DOI: 10.1111/j.1464-5491.1991.tb01581.x
|View full text |Cite
|
Sign up to set email alerts
|

No Deterioration of Oral Glucose Tolerance During Pregnancy in Rural Tanzania

Abstract: There is still controversy concerning the reference ranges for glucose tolerance tests in pregnancy. The WHO has recommended the universal use of the 75 g oral glucose load with 2-h post-load values of greater than 6.7 mmol l-1 to be considered impaired glucose tolerance (IGT) in the non-pregnant, and equivalent to gestational diabetes in the pregnant. Some data are available for pregnant Caucasians but little information is available for other ethnic groups. Oral glucose tolerance tests (75 g) have therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
2
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 5 publications
0
24
2
1
Order By: Relevance
“…This pattern contrasts with some earlier reports from the continent which showed either no change or showed an improvement in carbohydrate tolerance status. Our urban subjects might not have been comparable with rural subjects studied by Swai et al, (5). Glucose absorption in pregnancy is variable and thus results of OGTT may be difficult to reproduce.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…This pattern contrasts with some earlier reports from the continent which showed either no change or showed an improvement in carbohydrate tolerance status. Our urban subjects might not have been comparable with rural subjects studied by Swai et al, (5). Glucose absorption in pregnancy is variable and thus results of OGTT may be difficult to reproduce.…”
Section: Discussionmentioning
confidence: 46%
“…In Africa, the results of studies about carbohydrate metabolism in pregnancy have been disparate with some studies reporting deterioration as in the other parts of the world reporting. Some reports indicate an improvement in carbohydrate metabolism with advancing gestation age (3)(4)(5)(6)(7). There is consensus that fasting plasma glucose (FPG) levels are lower in the pregnant state than in the non-pregnant state especially in the early pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Of more direct relevance to our findings, Famuyiwa et al (7) also reported that in Nigerian women, FBG levels in the three trimesters and postpartum were significantly lower when compared with nonpregnant control subjects. In a more recent cross-sectional community survey in rural African women, we found that the mean FBG decreased progressively throughout pregnancy (6). The lower FBG values in pregnancy are presumably attributable to increased glucose utilization by the enlarging uteroplacental-fetal mass.…”
Section: Conclusion-our Results Thusmentioning
confidence: 93%
“…Thus, Jackson (4) in South Africa concluded that glucose tolerance was not often impaired in the course of normal pregnancy. In Kenya, Fraser (5), using the 50-g OGTT, showed an improvement in glucose homeostasis with advancing pregnancy, whereas Swai et al (6) in a cross-sectional rural communitybased study in Tanzania showed similar improvement. Famuyiwa et al (7) studied 20 normal, pregnant Nigerian women in each trimester and in the postpartum period, and found the highest mean blood glucose levels in the 2nd and 3rd trimesters.…”
mentioning
confidence: 81%
“…Zwei weitere Studien aus Tansania berichten von ähnlichen Ergebnissen, jedoch war auch hier die Anzahl der Studienteilnehmer relativ gering (89 bzw. 189) [21,22] .…”
Section: Die Dynamik Des Schwangerschaftsdiabetes In Ostafrikaunclassified